Android-Based Statistics Adventure Educational Games to Enhance Students’ Understanding of Measures of Central Tendency and ICT Literacy - Fatahillah, Arif; Ningsih, Mirah Wahyu; Monalisa, Lioni Anka; Kristiana, Arika Indah; Hussen, Saddam (Universitas Islam Negeri Sunan Kudus, 2025)
In the era of society 5.0, one of the essential skills students must possess is ICT literacy. This skill can be developed through the use of technology-integrated learning media. One of the technology-based learning media that can be used is educational games. This study aims to examine the effectiveness of the Statistics Adventure educational game in enhancing students' understanding of measures of central tendency and ICT literacy. The ICT literacy components assessed include access, manage, integrate, evaluate, and create. This research specifically focuses on the